The effect of antenatal lifestyle advice for women who are overweight or obese on secondary measures of neonatal body composition: the LIMIT randomised trial. (January 2016) - Dodd, JM; Deussen, AR; Mohamad, I; Rifas‐Shiman, SL; Yelland, LN; Louise, J; McPhee, AJ; Grivell, RM; Owens, JA; Gillman, MW; Robinson, JS
Abstract : Objective: To evaluate the effect of providing antenatal dietary and lifestyle advice on neonatal anthropometry, and to determine the inter‐observer variability in obtaining anthropometric measurements. Design: Randomised controlled trial. Setting: Public maternity hospitals across metropolitan Adelaide, South Australia. Population: Pregnant women with a singleton gestation between 10 +0 and 20 +0 weeks, and body mass index (BMI) ≥25 kg/m 2 . Methods: Women were randomised to either Lifestyle Advice (comprehensive dietary and lifestyle intervention over the course of pregnancy including dietary, exercise and behavioural strategies, delivered by a research dietician and research assistants) or continued Standard Care. Analyses were conducted using intention‐to‐treat principles. Main outcome measures: Secondary outcome measures for the trial included assessment of infant body composition using body circumference and skinfold thickness measurements (SFTM), percentage body fat, and bio‐impedance analysis of fat‐free mass. Results: Anthropometric measurements were obtained from 970 neonates (488 Lifestyle Advice Group, and 482 Standard Care Group). In 394 of these neonates (215 Lifestyle Advice Group, and 179 Standard Care Group) bio‐impedance analysis was also obtained. There were no statistically significant differences identified between those neonates born to women receiving Lifestyle Advice and those receiving Standard Care, in terms of body circumference measures, SFTM, percentage body fat, fat mass, or fat‐free mass. The intra‐class correlation coefficient for SFTM was moderate to excellent (0.55–0.88). Conclusions: Among neonates born to women who are overweight or obese, anthropometric measures of body composition were not modified by an antenatal dietary and lifestyle intervention. Tweetable abstract: Lifestyle advice in pregnancy does not modify body composition of infants of overweight and obese women. Tweetable abstract: Lifestyle advice in pregnancy does not modify body composition of infants of overweight and obese women.